수두차를 이용한 수저퇴적물 제거장치 개발에 관한 연구 - 이영길(Young-Gill Lee); 손충렬(Choong-Yul Son); 정우철(Uh-Cheul Jeong); 유진원(Jin-Won Yu); 정광열(Kwang-Leol Jeong); 김강신(Kang-Sin Kim); 김방열(Bang-Leol Kim) (大韓造船學會 論文集, 2008)
According to the existing research result on the seabed organic sediment, pollutants from the land and the sea contaminate the coastal water and sediment on the seabed. To tackle this problem, we need to dredge organic sediment. In the present paper, the development of removing system of seabed sediment by the difference of water head is researched by experimental method. For the validation of the decompression system, computations for validation are carried out for sediment removing equipment. The performance of inhalation equipment is analysed by some model tests.